Effect of protein–protein interactions and solvent viscosity on the rotational diffusion of proteins in crowded environments. Issue 2 (18th December 2018) - Nawrocki, Grzegorz; Karaboga, Alp; Sugita, Yuji; Feig, Michael
Abstract : Slow-down of the rotational diffusion of villin in the presence of villin crowder in close proximity. Abstract : The rotational diffusion of a protein in the presence of protein crowder molecules was analyzed via computer simulations. Cluster formation as a result of transient intermolecular contacts was identified as the dominant effect for reduced rotational diffusion upon crowding. The slow-down in diffusion was primarily correlated with direct protein–protein contacts rather than indirect interactions via shared hydration layers. But increased solvent viscosity due to crowding contributed to a lesser extent. Key protein–protein contacts correlated with a slow-down in diffusion involve largely interactions between charged and polar groups suggesting that the surface composition of a given protein and the resulting propensity for forming interactions with surrounding proteins in a crowded cellular environment may be the major determinant of its diffusive properties.